Clinical correlates of augmentation/combination treatment strategies in major depressive disorder. (28th February 2018) - Dold, M.; Bartova, L.; Mendlewicz, J.; Souery, D.; Serretti, A.; Porcelli, S.; Zohar, J.; Montgomery, S.; Kasper, S.
Abstract : Objective: This multicenter, multinational, cross‐sectional study aimed to investigate clinical characteristics and treatment outcomes associated with augmentation/combination treatment strategies in major depressive disorder (MDD). Method: Sociodemographic, clinical, and treatment features of 1410 adult MDD patients were compared between MDD patients treated with monotherapy and augmentation/combination medication using descriptive statistics, analyses of covariance (ancova ), and Spearman's correlation analyses. Results: 60.64% of all participants received augmentation and/or combination strategies with a mean number of 2.18 ± 1.22 simultaneously prescribed psychiatric drugs. We found male gender, older age, Caucasian descent, higher weight, low educational status, absence of occupation, psychotic symptoms, melancholic and atypical features, suicide risk, in‐patient treatment, longer duration of hospitalization, some psychiatric comorbidities (panic disorder, agoraphobia, obsessive‐compulsive disorder, and bulimia nervosa), comorbid somatic comorbidity in general and concurrent hypertension, thyroid dysfunction, diabetes, and heart disease in particular, higher current and retrospective Montgomery and Åsberg Depression Rating Scale total scores, treatment resistance, and higher antidepressant dosing to be significantly associated with augmentation/combination treatment. These findings were corroborated when examining the number of concurrently administered psychiatric drugs in the statistical analyses. Conclusion: Our findings suggest a clear association between augmentation/combination strategies and treatment‐resistant/difficult‐to‐treat MDD conditions characterized by severe symptomatology and high amount of psychiatric and somatic comorbidities.